Babymouse. [15], A very Babymouse Christmas - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2011)
Babymouse approaches the holidays with a single-minded determination to get the presents she wants.
3.3
3-6.
3-6
Keywords: Animals -- Comic books, strips, etc -- Juvenile fiction; Babymouse (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Animals -- Fiction; Babymouse (Fictitious character) -- Fiction; Cartoons and comics; Christmas -- Fiction; Mice -- Fiction; Animals -- Comic books, strips, etc -- Fiction; Babymouse (Fictional character) -- Comic books, strips, etc -- Fiction; Christmas -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Graphic novels; Mice -- Comic books, strips, etc -- Fiction; Christmas stories; Graphic novels